2020
DOI: 10.1002/ldr.3705
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil characteristics and bacterial communities to nitrogen fertilization gradients in a coastal salt‐affected agroecosystem

Abstract: Understanding the relationship between fertilization and soil bacterial communities in a salt-affected environment is essential for alleviating the adverse impact of excessive salinity on soil biochemical functioning. However, how soil bacterial communities respond to consecutive fertilization across nitrogen gradients in coastal agroecosystemhas not yet been clarified. We conducted a field plot experiment with four nitrogen fertilization rates (0, 150, 300, and 450 kg N hm −2 yr −1 ) on coastal salt-affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 60 publications
6
17
1
1
Order By: Relevance
“…Proteobacteria was the most abundant phyla across most RCST, while others with a relatively high abundance were Bacteroidetes, Acidobacteria and Actinobacteria. This finding is consistent with previous studies that profiled the abundant bacterial phyla in rice-cultivated mudflats [118,119]. An important observation in the distribution of bacteria across all RCST was the dominance of Proteobacteria and Acidobacteria in the rice cultivated PH soil in Chokwe and also the dominance of Bacteroidetes in the rice cultivated soil in Umbeluzi.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Proteobacteria was the most abundant phyla across most RCST, while others with a relatively high abundance were Bacteroidetes, Acidobacteria and Actinobacteria. This finding is consistent with previous studies that profiled the abundant bacterial phyla in rice-cultivated mudflats [118,119]. An important observation in the distribution of bacteria across all RCST was the dominance of Proteobacteria and Acidobacteria in the rice cultivated PH soil in Chokwe and also the dominance of Bacteroidetes in the rice cultivated soil in Umbeluzi.…”
Section: Discussionsupporting
confidence: 92%
“…Investigation of bacterial species-environment relationship revealed that ammonium (NH 4 + ), nitrate (NO 3 − ), total nitrogen, P-Olsen, moisture, SOC, pH and electrical conductivity (EC) significantly (p < 0.05) influenced the bacterial communities (Table S4). Changes in physicochemical parameters have been severally reported to have a strong influence on bacterial community structure in diverse environments [17,84,115,118]. The impact of some of these physicochemical terms and the microbial community changes they drive in rice-cultivated soils have been extensively reviewed [94].…”
Section: Discussionmentioning
confidence: 99%
“…However, HIS increased nitrogen consumption, which was the same as in HIM and HII. Although the nutrient consumption of HIS did not cause significant between-group differences in our study, the relationship between soil nitrogen content and bacterial communities involved in nitrogen cycling indicated that HIS exhibited oligotrophic status and increased nitrogen consumption [14,[48][49][50][51][52]. The reason may be that forage grass enhances nitrogen cycling and causes nitrogen loss via nitrite reduction [69].…”
Section: The Risks and Benefits Of Planting Forage Grass On Lacontrasting
confidence: 55%
“…In 2016 and 2017, HIS had significant effects on some oligotrophic bacteria, including Acidobacteria Gp3, Gemm-4, NB1-I, Polaromonas, and Novosphingobium (LDA score > 2, K-W test P < 0.05) [14,[48][49][50]. In 2018, some bacteria involved in nitrogen cycling and plantgrowth promotion increased in the HIS, including Solibacteres, Planctomycetia, Sva0725, Rubrivivax, and Nitrospira (LDA score > 2, K-W test P < 0.05) [51][52][53]. In terms of fungi, some fungi associated with AMF and endomycorrhizae formation were promoted in HIS in 2017 and 2018, including Diversisporales, Tuberaceae, and Acaulospora (LDA score > 2, K-W test P < 0.05) [46,47,54].…”
Section: The Effects Of Management Scenarios On Microbial Communitiesmentioning
confidence: 99%
“…However, the effects of N and/or P fertilizer application on microbial diversity and composition were currently inconsistent among various studies. Yao et al (2021) reported that soil bacterial community richness increased with N application rate in a coastal salt-affected agroecosystem.…”
mentioning
confidence: 99%